Geospatial and Community Participation Combination in Complete Systematic Land Registration Implementation in Hulu Sungai Tengah Regency - Sa’dianoor Sa’dianoor; Linus Yoseph Wawan Rukmono; Edy Saptono; Moelyanto Moelyanto; Irdam Ahmad; Sobar Sutisna; Syamsul Maarif (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Land certification provides land legal certainty for every citizen of the Republic of Indonesia, especially, farmers, who constitute the majority of the population of Indonesia. The importance of the agricultural land has been explained in the Republic of Indonesia’s Defense White Paper that the growing amount of agricultural land has a detrimental effect on the Indonesian nation which is agrarian. Decreasing agricultural land is the main factor causing reduced food security. Geospatial technologies such as remote sensing and terrestrial surveys are very helpful for Complete Systematic Land Registration (PTSL) activities. However, the implementation in the field of technology has not yet been optimized due to the lack of the support from Regional Government and the Community. By taking the PTSL implementation in two villages in Barabai Subdistrict, Hulu Sungai Tengah Regency, it was found that problems related to the absence of certaintyof village boundaries, accurate and scattered control points and community understanding of the importance of the legality of their land are inhibiting factors for PTSL activities. By combining this technology with community participation it will produce the right and ideal combination.